Стан деревних рослин у паркових насадженнях промислових міст південного сходу України - Суслова, О.П.; Поляков, О.К.; Хархота, Л.В. (Промышленная ботаника, 2013)
Приведены данные обследования парковых насаждений промышленных городов юго-востока Украины. Определен видовой состав (186 видов и культиваров), возрастная структура и состояние древесных растений. Выявлена зависимость жизнеспособности деревьев разной интенсивности роста от их возраста. The data obtained in the course of surveying park stands of industrial cities in the south-east of Ukraine are presented. The specific composition (186 species and cultivars), age structure and health condition of these stands were determined. The study has revealed correlation between viability of the trees with different growth intensity and their age.